The role of the district reading program coordinator in Newfoundland and Labrador as perceived by primary and elementary teachers and by reading program coordinators - Jarvis, Theresa, 1956- (1987)
Thesis (M.Ed)--Memorial University of Newfoundland, 1987. Education Bibliography: leaves 112-119. The purpose of this study was to analyze the role of the reading program coordinator in an attempt to determine whether the reading program coordinator's perception of his/her role differed significantly from the primary elementary classroom teacher's perception of the reading coordinator’s role. The overall aim of this study was to help clarify the role of the reading program coordinator in Newfoundland and Labrador. More specifically, the study attempted to determine the following: (a) the role of the reading coordinator as discussed in the literature; (b) primary/elementary teachers’ and Reading coordinators’ perceptions of the role of the reading coordinator in Newfoundland and Labrador; (c) primary/elementary teachers' and reading coordinators' perceptions regarding the importance of the role of the district reading coordinator; and (d) primary/elementary teachers' and reading coordinators' perceptions regarding the distribution of the reading coordinator's time. -- Two methods of gathering data were employed. First, literature related to the role of the reading coordinator was analyzed to help define the role of the reading coordinator. Second, data was obtained from responses to two questionnaires which were administered to reading coordinators and classroom teachers. The questionnaire consisted of thirty-eight tasks and three categories of task areas: (a) Knowledge Area; (b) Interpersonal Skills and Attitudes; and (c) Administrative and Organizational Activities. The data from the questionnaire was analyzed for each of the three categories of tasks. The questionnaire also required repsondents to indicate their perceptions of the importance of the role of the district reading coordinator and their perceptions regarding distribution of the reading coordinator's time. -- The findings from this study have shown that the reading coordinator's own role conception differs from the classroom teacher's perception of the reading coordinator's role. Reading coordinators were very positive in their perceptions of their performance, whereas, classroom teachers were less positive in their perceptions of the reading coordinator's performance. -- Findings from this study have implications for reading coordinators, the Department of Education and school boards in Newfoundland and Labrador. Since the reading coordinator's role is influenced by the perceptions and expectations of others, he/she should be aware of the perceptions of significant others for his/her role. A Job description should be written for the reading coordinator's role. This would help clarify the role for reading coordinators and other school personnel related to his/her position.